2020
DOI: 10.1080/08039488.2020.1862296
|View full text |Cite
|
Sign up to set email alerts
|

Does baseline leisure-time physical activity level predict future depressive symptoms or physical activity among depressive patients? Findings from a Finnish five-year cohort study

Abstract: Objectives: The aims of this study were to investigate whether baseline leisure-time physical activity (LTPA) is associated with future recovery from depression among patients with a depression diagnosis and whether baseline LTPA is associated with total physical activity after five years of follow-up. Methods: A total of 258 patients aged 35 years with clinically confirmed depression at baseline participated. The study was conducted between 2008 and 2016 in municipalities within the Central Finland Hospital D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…There is abundant evidence that the antidepressant effects could emerge with non-medical intervention represented by leisure-time physical activity (LPA) in teenagers' ( 9 11 ), middle-aged ( 12 ) and elder ( 13 15 ) groups. A recent meta-analysis, which included 49 unique prospective cohort studies and 266,939 participants, found that people with high levels of physical activity had lower odds of developing depression compared with low levels (adjusted OR = 0.83, 95% CI: 0.79 ~ 0.88; I 2 = 0.00) ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is abundant evidence that the antidepressant effects could emerge with non-medical intervention represented by leisure-time physical activity (LPA) in teenagers' ( 9 11 ), middle-aged ( 12 ) and elder ( 13 15 ) groups. A recent meta-analysis, which included 49 unique prospective cohort studies and 266,939 participants, found that people with high levels of physical activity had lower odds of developing depression compared with low levels (adjusted OR = 0.83, 95% CI: 0.79 ~ 0.88; I 2 = 0.00) ( 16 ).…”
Section: Introductionmentioning
confidence: 99%